A multi-scenario approach for a robust design of solar-based ORC systems. (December 2020) - Petrollese, Mario; Cocco, Daniele
Abstract: The application of Organic Rankine cycle (ORC) units in concentrating solar power systems is a very promising solution. However, fluctuations in the available solar energy often force solar-based ORC systems to operate at off-design conditions. An innovative methodology for finding robust design solutions of such ORC systems, based on the minimization of the expected Levelized Cost of Energy (LCOE), is therefore proposed. The expected variations in the ORC heat source and heat sink are considered during the design stage by adopting a multi-scenario approach. The proposed methodology has been tested by referring to a medium-scale ORC unit and by considering different working fluids. As case studies, the direct coupling of the ORC unit with a solar field and the integration of a thermal energy storage system have been investigated. The comparison of the results obtained by using a multi-scenario and a single-scenario approach highlights a reduction of the actual LCOE. The ORC configuration obtained by adopting a multi-scenario approach is characterized by lower performance under design conditions, but it is less sensitive to variations in the main inputs during off-design operating periods. This fact is particularly noteworthy for the case with the direct coupling of the solar field. Highlights: An innovative approach for the robust design of ORC units fed by solar energy. Involvement of solar irradiance and air temperature variations during design stage. Five cases study with or without the inclusion of TES systems are analyzed. ORC units with lower design performance but less sensitive to boundary variations. The effectiveness of the proposed approach improves with the variability of inputs.